Effects of a sedative antihistamine, D-chlorpheniramine, on regional cerebral perfusion and performance during simulated car driving - Tashiro, Manabu; Sakurada, Yumiko; Mochizuki, Hideki; Horikawa, Etsuo; Maruyama, Masahiro; Okamura, Nobuyuki; Watanuki, Shoichi; Arai, Hiroyuki; Itoh, Masatoshi; Yanai, Kazuhiko (Human psychopharmacology, 2008)
Objectives The sedative side effects of antihistamines have been recognized to be potentially dangerous in car driving, but the mechanism underlying these effects has not yet been elucidated to date. The aim of the present study is to examine regional cerebral blood flow (rCBF) responses during a simulated car‐driving task following oral administration of D‐chlorpheniramine using positron emission tomography (PET) and [15O]H2O, based on a single‐blind cross‐over study‐design. Methods Right‐handed, healthy male volunteers (n = 14) drove a car in a simulated environment following oral administration of D‐chlorpheniramine repetab 6 mg or placebo. Their rCBF was measured using PET with [15O]H2O in the following three conditions: (1) resting, (2) active driving, and (3) passive driving. All ‘in‐car’ views during the simulated driving were videotaped and used for rating driving performance. Results Performance evaluation revealed that the number of lane deviations significantly increased in the D‐chlorpheniramine condition compared with the placebo condition (p < 0.01). Subjective sleepiness was not significantly different between the two drug conditions. The regions of diminished brain responses following D‐chlorpheniramine treatment were detected in the parietal, temporal and visual cortices, and in the cerebellum. The regions of augmented rCBF responses were found in the orbitofrontal cortex and cerebellar vermis. Conclusion These results suggest that D‐chlorpheniramine tends to suppress visuo‐spatial cognition and visuo‐motor coordinating functions rather than attention and motor functions during car driving. Copyright © 2008 John Wiley & Sons, Ltd.